Statement 710399 - Hodzic, Refik (Bosnia and Hercegovina, 2006)
Verzio FF submission The story of a father trying to find out what happened to his son who slipped out of his hands and dissapeared during the Srebrenica genocide as well as a story of Bosnia and Herzegovina, a country permanently scarred by war crimes and their legacy.